Hybrid femtosecond/picosecond coherent anti‐Stokes Raman scattering for high‐speed CH4/N2 measurements in binary gas mixtures1. (27th February 2013) - Engel, Sascha R.; Miller, Joseph D.; Dedic, Chloe E.; Seeger, Thomas; Leipertz, Alfred; Meyer, Terrence R.
Abstract : Hybrid femtosecond/picosecond (fs/ps) vibrational coherent anti‐Stokes Raman scattering was demonstrated for high‐speed, in‐situ measurements of CH4 /N2 mole fractions in binary gas mixtures with temporal nonresonant suppression. A single broadband, 100‐fs laser source was used to simultaneously excite CH4 and N2 vibrational Raman transitions, characterized by a spectral separation of 584 cm −1, followed by frequency‐domain detection with a time‐delayed ps probe pulse. In this manner, the temporal evolution of the nonresonant background and vibrational wavepackets of CH4 and N2 could be evaluated to maximize signal and minimize interferences. A typical accuracy of 95% was achieved for experimental CH4 mole fractions between 0.02 and 0.70, and a precision of 4% was achieved by maximizing relative excitation energy through induced chirp in the pump and Stokes pulses. It was further shown that mole‐fraction measurements were not affected by variations in bi‐molecular broadened linewidths over a wide range of mixture fractions. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Hybrid femtosecond/picosecond vibrational coherent anti‐Stokes Raman scattering was demonstrated for high‐speed, in situ measurements of CH4 /N2 mole fractions in binary gas mixtures with temporal nonresonant suppression. A typical accuracy of 95% was achieved for CH4 mole fractions from 0.02‐0.70, and a precision of 4% was achieved by maximizing relative excitation energy through induced chirp in the pump and Stokes pulses. Furthermore, mole fraction measurements were not affected by variations in bi‐molecular broadened linewidths over a wide range of mixture fractions.